Квазіоптимальна стабілізація лінійних керованих сингулярно збурених систем із запізненням - Клевчук, І.І.; Щур, О.І. (Кам’янець-Подільський національний університет імені Івана Огієнка, 2024)
We consider a linear singularly perturbed system of difference-differential equations with control. We obtain a representation of an integral manifolds of this system. We search the solution of the problem of quasioptimal stabilization in the form of expansion into a power series about ε.
Keywords: stabilization linear controlled systems delay